Cytotoxic sesquiterpenoids from Dysoxylum parasiticum (Osbeck) Kosterm. stem bark. (February 2022) - Arofatus Naini, Al; Mayanti, Tri; Nurlelasari,; Harneti, Desi; Maharani, Rani; Safari, Agus; Hidayat, Ace Tatang; Farabi, Kindi; Lesmana, Ronny; Supratman, Unang; Shiono, Yoshihito
Graphical abstract: Highlights: Five sesquiterpenoids (1 - 5 ), were isolated from Dysoxylum parasiticum (Osbeck) Kosterm. stem bark. The structures were elucidated using NMR and HR-TOFMS spectroscopic data. Sesquiterpenoids (1 - 5), were tested for their cytotoxic effects against the MCF-7 cell. Compound 4, showed the strongest activity with an IC50 value of 12.7 μM. Abstract: Two undescribed sesquiterpenoid derivatives, 10 β, 11-dihydroxy-1 β -hydroperoxide-4 αH, 5 αH, 7 βH -guaiane (1 ) and 10 β -hydroxy-4 α, 4 β -dimethyl-5 αH, 7 αH- eudesm-3-one (2 ) along with three known of guaiane, aromadendrane, and cadinane sesquiterpenoids (3 -5 ) were isolated from the stem bark of Dysoxylum parasiticum (Osbeck) Kosterm. The chemical structure of the compounds were determined by detailed analysis of spectroscopic data, including MS, IR, 1D, and 2D NMR as well as through comparison with data of known analogues. The isolated compounds were also tested for cytotoxic properties against MCF-7 breast cancer line. Compound 4, was found to exhibit the strongest cytotoxic activity with an IC50 value of 12.17 μM, while the other compounds showed moderate or no activity.